Education Studies and the uses of Literary Form: towards student engagement with educational theory - John Grant (Educational Futures)
This article, by the employment of a novel theoretical framework, examines the value of introducing short stories to students of education and champions the literary genre of the short story. These stories provide convenient material to engage and enthuse Education Studies students and to position undergraduates at the nucleus of an Education Studies programme. Firstly, an examination explores and clarifies the emergence of this novel framework, entitled The Four Pillars for Education Theory, before moving on to critically examine an extensive overview of Education Studies and the inherent themes and arguments suggested by writers within the field. In addition, this piece will discuss the motivations, that is, the inspirational influences that set out the reasoning to underpin the value of introducing worthwhile literature to students of Education. Furthermore, it provides a working example of how this material can be implemented as convenient seminar discussion material.